STRATEGIC KNOWLEDGE AND MIGRATION MANAGEMENT SOCIAL, POLITICAL, HEALTH AND INTERNATIONAL ASPECTS - Manev, GJorgji; Georgiev, Antonio; Marijan Stevanovski (MIT University Skopje, 2016)
The occurrence of strong military conflicts and unsafe living on the territory of the Middle East generated a refugee’s crisis, the refugees heading for the well-off European Union member states. The purpose of this paper is to study this phenomenon and to offer strategic proposals and know-how in order to handle the crisis and to restore safety and security both there and in our country. This paper deals with the background and development of the migration process, as well as with the ways in which the world and the Republic of Macedonia are trying to manage this far from slight crisis. The paper also gives some strategic guidelines for further actions and approaches that will ensure weakening of the tensions and better cooperation and development.
Keywords: Refugees; Migrations; Health Care; Strategic Knowledge; Strategies in a situation of crisis